Answer:
Ca2+(aq) + 2OH-(aq) → Ca(OH) 2 ( s )
Step-by-step explanation:
The balanced equation is given as;
Ca(NO 3 ) 2 ( aq ) + 2KOH(aq) → Ca(OH) 2 ( s ) + 2KNO 3 ( aq )
The net ionic equation features only ions that actually participated in the reaction. These ions are identified due to their change in oxidation numbers. Also, the aqueous compounds are broken down into ions.
Ca2+ + 2NO3- + 2K+ + 2OH- → Ca(OH) 2 ( s ) + 2K+ + 2NO3-
Ions present in both sides of the equation above. These are; NO3-, K+ and OH-
The net ionic equation is;
Ca2+(aq) + 2OH-(aq) → Ca(OH) 2 ( s )